2022
DOI: 10.20525/ijrbs.v11i5.1880
|View full text |Cite
|
Sign up to set email alerts
|

The antecedents of repurchase intention in Indonesian e-commerce marketplace customers during the COVID-19 pandemic with age as a moderating variable: A study on e-commerce marketplace customers in Java

Abstract: This study aims to examine the factors that affect customers repurchase intention in the e-commerce marketplace during the COVID-19 pandemic on Java Island in Indonesia, using the extended Technology Acceptance Model (TAM) theory and UI/UX Concept. Perceived ease of use, shopping experience, e-trust, and age are variables that are predicted to affect e-commerce marketplace repurchase intention behavior during the COVID-19 pandemic. The data were collected through an online survey from e-commerce marketplace cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
1
4
0
1
Order By: Relevance
“…Instead, consumers turn to the merchant's website for information about products. The previous research about consumer online shopping behaviour found that electronic trust has a significant positive impact on consumer online purchase intention [ 27 ]. They also stated that no users or consumers will buy products from untrusted e-commerce merchants even though they may feel satisfied with the products and services provided.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, consumers turn to the merchant's website for information about products. The previous research about consumer online shopping behaviour found that electronic trust has a significant positive impact on consumer online purchase intention [ 27 ]. They also stated that no users or consumers will buy products from untrusted e-commerce merchants even though they may feel satisfied with the products and services provided.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They also stated that when the presenter or influencer presents the products via live streaming, the consumer can easily see the details of the products and get accurate information about them; this proves that the perceived utilitarian value affects consumer trust in the presenter as well as the platform. Consumers tend to lose confidence in using technology when they find it difficult to use it [ 27 ].…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…A., 2014). The CUE model, or Components of User Experience, (Thüring & Mahlke, 2007) and the Technology Acceptance Model (TAM) (Kim et al, 2009;McKinney et al, 2002;Thüring & Mahlke, 2007;Dewi et al, 2022) are two of the foundational models upon which the EUX-DM was built. The verified 'EUX-DM' was used to assess four major facets of User Experience (UX) (Fig.…”
Section: Measurementmentioning
confidence: 99%
“…Pembeli harus memperhatikan berbagai aspek saat hendak mengunjungi tempat berbelanja seperti penggunaan masker, hand sanitizer, dan bagaimana cara untuk meminimalisir kontak fisik. Perubahan ini tentunya memengaruhi pola belanja masyarakat (Dewi et al, 2022;Guo et al, 2020) yang semula berbelanja secara langsung, menjadi tidak langsung (secara online). Salah satu platform yang digunakan untuk kegiatan perdagangan secara online adalah aplikasi e-commerce (Tudor, 2022).…”
Section: Pendahuluanunclassified